Antimicrobial resistance and typing of Salmonella isolated from street vended foods and associated environment - Anukampa (J Food Sci Technol, 2017)
The present study was carried out to find out the occurrence and types of Salmonella present in street vended foods and associated environment, and their resistance pattern against various antibiotics. About 1075 street vended food and associated environment samples were processed for isolation and confirmation of different Salmonella spp. by targeting gene specific invA gene and serotype specific Sdf I, Via B and Spy genes by PCR. Selected Salmonella isolates were screened for antibiotic resistance by using Baeur–Kirby disk diffusion test. Out of 1075 samples, only 31 (2.88%) isolates could be amplified the invA gene of which 19 could be recovered from meat vendors; 8 from egg vendors while remaining 4 from milk vendors. Though, majority of Salmonella recovered from raw foods the ready-to-eat food like chicken gravy and rasmalai also showed its presence which pose a serious public health threat. Overall, 19, 6 and 1 isolates of S. Typhimurium, S. Enteritidis and S. Typhi could be detected by PCR while remaining 5 isolates could not be amplified suggesting other type of Salmonella. Selected Salmonella isolates were completely resistance to Oxacillin (100%) followed by Cefoxitin (30.43%) and Ampicillin (26.10%). Thus, it is observed that the street vended foods of animal origin and associated environment play an important role in transmission of food borne pathogens including Salmonella.